2016
DOI: 10.1016/j.asej.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Improved confinement of reinforced concrete columns

Abstract: Traditional steel ties reinforcement cannot provide superior confinement for reinforced concrete (RC) columns due to the constraints on tie spacing and disturbance of concrete continuity. This paper presents a practical confinement configuration consisting of single Expanded Metal Mesh (EMM) layer in additional to regular tie reinforcement. The EMM layer is warped above ties. The proposed transverse reinforcement, with various volumetric ratios of ties, was investigated in sixteen square short RC column specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 8 publications
1
15
0
2
Order By: Relevance
“…22 and 23. This result agrees with the research introduced by El-Kholy and Dahish [22], which showed a significant improvement in the ultimate load of the RC columns by using steel mesh as internal confinement.…”
Section: Load Versus Vertical Shortening Curves and Maximum Loadsupporting
confidence: 92%
See 1 more Smart Citation
“…22 and 23. This result agrees with the research introduced by El-Kholy and Dahish [22], which showed a significant improvement in the ultimate load of the RC columns by using steel mesh as internal confinement.…”
Section: Load Versus Vertical Shortening Curves and Maximum Loadsupporting
confidence: 92%
“…Additionally, the strengthened specimens showed lower lateral displacements and higher ultimate load than the unstrengthened specimens because of the confinement effect using SSWM, which was more economical compared to using FRP. El-Kholy and Dahish [22] proposed an actual confinement arrangement consisted in using one layer of expanded mesh that was warped over the stirrups, which were used with different volumetric ratios in square RC columns. The confined columns showed higher plastic deformation, larger failure load, superior ductile performance, a greater capacity of energy absorption, and a larger decrease in the stirrups volumetric ratio compared to the unconfined columns.…”
Section: Introductionmentioning
confidence: 99%
“…Equations for calculating the capacity of the columns were proposed. El-Kholy and Dahish [22] reinforced sixteen short square RC column specimens of slenderness ratios k = 7.33 and 14 laterally with various volumetric ratios of ties. The confinement of twelve column specimens was enhanced by warping single expanded metal mesh layer around the ties.…”
Section: Introductionmentioning
confidence: 99%
“…Other relatively low tensile strengths of materials i.e. polyethylene/PE fibers (240 MPa) and wire mesh (320 MPa) have also been used to produce textile reinforcements [12][13]. Off course high tensile strength is beneficial to obtain high strength-high ductility of TRC as compared to those of fibers with low tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…higher than C (13%) but lower than AR glass (33%). Other researchers [12][13] used wire mesh as reinforcement of mortar in a similar manner to that of TRC.…”
Section: Introductionmentioning
confidence: 99%